Quantification of myocardial blood flow with dynamic perfusion 3.0 Tesla MRI: Validation with 15o‐water PET. Issue 3 (30th December 2014) - Tomiyama, Yuuki; Manabe, Osamu; Oyama‐Manabe, Noriko; Naya, Masanao; Sugimori, Hiroyuki; Hirata, Kenji; Mori, Yuki; Tsutsui, Hiroyuki; Kudo, Kohsuke; Tamaki, Nagara; Katoh, Chietsugu
<x xml:space="preserve">Abstract</x> Background To develop and validate a method for quantifying myocardial blood flow (MBF) using dynamic perfusion magnetic resonance imaging (MBFMRI) at 3.0 Tesla (T) and compare the findings with those of 15O‐water positron emission tomography (MBFPET). Methods Twenty healthy male volunteers underwent magnetic resonance imaging (MRI) and 15O‐water positron emission tomography (PET) at rest and during adenosine triphosphate infusion. The single‐tissue compartment model was used to estimate the inflow rate constant (K1). We estimated the extraction fraction of Gd‐DTPA using K1 and MBF values obtained from 15O‐water PET for the first 10 subjects. For validation, we calculated MBFMRI values for the remaining 10 subjects and compared them with the MBFPET values. In addition, we compared MBFMRI values of 10 patients with coronary artery disease with those of healthy subjects. Results The mean resting and stress MBFMRI values were 0.76 ± 0.10 and 3.04 ± 0.82 mL/min/g, respectively, and showed excellent correlation with the mean MBFPET values (r = 0.96, P < 0.01). The mean stress MBFMRI value was significantly lower for the patients (1.92 ± 0.37) than for the healthy subjects (P < 0.001). Conclusion The use of dynamic perfusion MRI at 3T is useful for estimating MBF and can be applied for patients with coronary artery disease. J. Magn. Reson. Imaging 2015;42:754–762.